DNA polymerase hybrids derived from the family-B enzymes of Pyrococcus furiosus and Thermococcus kodakarensis: improving performance in the polymerase chain reaction - Elshawadfy, Ashraf M.; Keith, Brian J.; Ee Ooi, H'Ng; Kinsman, Thomas; Heslop, Pauline; Connolly, Bernard A. (Frontiers in Microbiology, 2014)
The polymerase chain reaction (PCR) is widely applied across the biosciences, with archaeal Family-B DNA polymerases being preferred, due to their high thermostability and fidelity. The enzyme from Pyrococcus furiosus (Pfu-Pol) is more frequently used than the similar protein from Thermococcus kodakarensis (Tkod-Pol), despite the latter having better PCR performance. Here the two polymerases have been comprehensively compared, confirming that Tkod-Pol: 1) extends primer-templates more rapidly; 2) has higher processivity; 3) demonstrates superior performance in normal and real time PCR. However, Tkod-Pol is less thermostable than Pfu-Pol and both enzymes have equal fidelities. To understand the favourable properties of Tkod-Pol, hybrid proteins have been prepared. Single, double and triple mutations were used to site arginines, present at the “forked-point” (the junction of the exonuclease and polymerase channels) of Tkod-Pol, at the corresponding locations in Pfu-Pol, slightly improving PCR performance. The Pfu-Pol thumb domain, responsible for double-stranded DNA binding, has been entirely replaced with that from Tkod-Pol, again giving better PCR properties. Combining the “forked-point” and thumb swap mutations resulted in a marked increase in PCR capability, maintenance of high fidelity and retention of the superior thermostability associated with Pfu-Pol. However, even the arginine/thumb swap mutant falls short of Tkod-Pol in PCR, suggesting further improvement within the Pfu-Pol framework is attainable. The significance of this work is the observation that improvements in PCR performance are easily attainable by blending elements from closely related archaeal polymerases, an approach that may, in future, be extended by using more polymerases from these organisms.